2016
DOI: 10.4274/tjo.73645
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Metastasis of Multiple Myeloma: Case Report

Abstract: A 68-year-old woman with a history of multiple myeloma presented to the clinic with pain and vision loss in her right eye. Proptosis was observed in her right eye and eye movements were restricted in all directions. Best corrected visual acuity was 3/10 in her right eye. On biomicroscopic examination, hyperemia and subconjunctival hemorrhage were present. Fundus examination of the right eye revealed optic disc edema and choroidal folds. In magnetic resonance imaging two orbital masses were detected. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
1
7
0
2
Order By: Relevance
“…There are no prescribed guidelines for the management of such cases, however, radiotherapy followed by systemic chemotherapy has been the mainstay of treatment in cases of MM with orbital involvement. [ 6 10 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…There are no prescribed guidelines for the management of such cases, however, radiotherapy followed by systemic chemotherapy has been the mainstay of treatment in cases of MM with orbital involvement. [ 6 10 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Orbital plasmasitomlarda genellikle kemik tutulumu da meydana gelir (6). Seyrek olmasına rağmen literatürde orbital tutulum bildirilmiştir (3,7,8). Literatürdeki bu tutulumlar rastlantısal olarak bildirilmiştir.…”
Section: Discussionunclassified
“…Diffuse orbital disease as the presenting sign of recurrent MM has been described in other patients. Vatansever et al reported a case of new-onset proptosis with diffuse orbital metastasis, which included the extraocular muscles, globe and optic nerve after 5 years of disease remission 2. Thoumazet et al also described a case of diffuse inferior and temporal orbital and maxillary sinus plasmacytomas after 17 months of remission 8.…”
Section: Discussionmentioning
confidence: 99%
“…At the current point in time, the most favoured treatment approach to all patients with orbital disease is combination therapy typically utilising chemotherapy, radiation, steroids and stem-cell transplantation 1 2 4 7–10. However, Painter et al described successful treatment of an extramedullary plasmacytoma with dexamethasone injections 11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation